To identify the non-biological causes of child mortalities in developing countries, Social Autopsy tools should be based on “The Pathway to Survival Conceptual Framework” - Siddiqui, Muhammad Bilal; Wan Ng, Chiu; Wah Yun Low (International Journal of Endorsing Health Science Research, 2017)
Since a large proportion of child deaths occur due to preventable diseases in developing countries, estimating the cause of death (CoD) is very important for such prevention. Verbal Autopsy (VA) has given us tremendous amount of valuable data on the cause of death; however, VA data is primarily limited to assigning only biological cause of death (BCoD) to the unregistered child mortalities. Apart from gaining the information on BCoD, knowing the social or non-biological determinants (NBDs) linked with health care seeking behavior, health care delivery and access to health care to any child is of utmost importance. This knowledge potentially may help us to develop interventions targeting effects of different barriers affecting the timely and appropriate health delivery to the needy, thereby may help us by armoring us with new and more advanced information to prevent the child mortalities and improving the child survival estimates in developing geographies, which have huge inconsistencies related to social determinants of health. The concept of capturing NBDs and relating them with the death incidents in children has been backed in the literature.